PENGARUH TANGIBLE DAN EMPATHY TERHADAP KEPUASAN PENGUNJUNG PADA DESTINASI PARIWISATA AIR PANAS BANJAR - Putu Ayodhia Darsinita; Putra, Komang Endrawan Sumadi (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This study aims to explain the influence of tangible and empathy on customer satisfaction. The population in this study is the community that has visited the Air Panas Banjar tourist destination in Buleleng Regency. The sample size used is 400 people with the sampling method being simple random sampling. The analysis technique used is multiple linear regression analysis using SPSS 25. The results of this study indicate that tangible and empathy have a significant effect on customer satisfaction, tangible has a positive and significant effect on customer satisfaction, and empathy has a positive and significant effect on customer satisfaction. Therefore, it is important for the management of the Air Panas Banjar tourist destination to pay attention to tangible and empathy in order to build a positive attitude that ultimately impacts customer satisfaction.